Acod1-mediated inhibition of aerobic glycolysis suppresses osteoclast differentiation and attenuates bone erosion in arthritis - Kachler, Katerina; Andreev, Darja; Thapa, Shreeya; Royzman, Dmytro; Gießl, Andreas; Karuppusamy, Shobika; Llerins Perez, Mireia; Liu, Mengdan; Hofmann, Jörg; Geßner, Arne; Meng, Xianyi; Rauber, Simon; et al. (Annals of the Rheumatic Diseases, 2024)
Objectives: Metabolic changes are crucially involved in osteoclast development and may contribute to bone degradation in rheumatoid arthritis (RA). The enzyme aconitate decarboxylase 1 (Acod1) is known to link the cellular function of monocyte-derived macrophages to their metabolic status. As osteoclasts derive from the monocyte lineage, we hypothesised a role for Acod1 and its metabolite itaconate in osteoclast differentiation and arthritis-associated bone loss. Methods: Itaconate levels were measured in human peripheral blood mononuclear cells (PBMCs) of patients with RA and healthy controls by mass spectrometry. Human and murine osteoclasts were treated with the itaconate derivative 4-octyl-itaconate (4-OI) in vitro. We examined the impact of Acod1-deficiency and 4-OI treatment on bone erosion in mice using K/BxN serum-induced arthritis and human TNF transgenic (hTNFtg) mice. SCENITH and extracellular flux analyses were used to evaluate the metabolic activity of osteoclasts and osteoclast progenitors. Acod1-dependent and itaconate-dependent changes in the osteoclast transcriptome were identified by RNA sequencing. CRISPR/Cas9 gene editing was used to investigate the role of hypoxia-inducible factor (Hif)-1α in Acod1-mediated regulation of osteoclast development. Results: Itaconate levels in PBMCs from patients with RA were inversely correlated with disease activity. Acod1-deficient mice exhibited increased osteoclast numbers and bone erosion in experimental arthritis while 4-OI treatment alleviated inflammatory bone loss in vivo and inhibited human and murine osteoclast differentiation in vitro. Mechanistically, Acod1 suppressed osteoclast differentiation by inhibiting succinate dehydrogenase-dependent production of reactive oxygen species and Hif1α-mediated induction of aerobic glycolysis. Conclusion: Acod1 and itaconate are crucial regulators of osteoclast differentiation and bone loss in inflammatory arthritis.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Arthritis; Experimental; Arthritis; Rheumatoid; Bone Density; Inflammation; Osteoporosis